POPULATION ASSESSMENT OF JAVAN BELIDA FISH (Notopterus notopterus) IN RAWA PENING LAKE, CENTRAL JAVA, INDONESIA - Waluyo waluyo; Santoso Budi Widiarto; Anhar Muslim; Linggar Dirgantara; Alyaa Farah Qonitah; Ela Anjarwati; Darmawan Darmawan (BIOTROPIA, 2026)
ARTICLE HIGHLIGHT- Belida population in the lake is low and nearing threatened status.- Belida size data show weak population recovery.- Conservation action is needed to protect belida stocks.- Habitat pressure increases belida vulnerability and limits protection.- Findings support stronger conservation for threatened belida.ABSTRACTThe conservation status of belida fish in Indonesia is regulated under the Minister of Maritime Affairs and Fisheries of the Republic of Indonesia Number 1 of 2021 concerning Protected Fish Types, which includes four species: Bornean Belida (Chitala borneensis), Sumatran Belida (Chitala hypselonotus), Lopis Belida (Chitala lopis), and Java belida (Notopterus notopterus). The Javan belida fish (Notopterus notopterus) is currently classified as Least Concern (LC) to facilitate data collection on protected fish species and those listed in the Appendices of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). However, intensive harvesting for human consumption may lead to continued population declines in Java. Therefore, this study aimed to estimate the population size and status of the Javan belida fish, providing a scientific basis for government recommendations, particularly by the Ministry of Maritime Affairs and Fisheries, regarding its conservation status. Field sampling was conducted in situ in Rawa Pening Lake during three sampling periods (January, February, and March 2024) using bamboo blinds, traps, and lift nets. The collected data were analyzed to estimate population abundance, length-weight relationships, length-frequency distribution, sex ratio, gonad maturity stage, and catch per unit of effort. A total of 47 belida fish were caught, all identified as Javan belida (Notopterus notopterus). The estimated population density in Rawa Pening Lake was 32 individuals per 1,400 m2, equivalent to 229 individuals per ha. Based on the International Union for Conservation of Nature's (IUCN) vulnerability criteria, the belida population in Rawa Pening Lake is considered near threatened.